Colourful Packaged Snacks Consumed by Children and Adolescents in Turkey: Colourants, Fats, and Sustainability Labels - Ayşegül Sivaslıoğlu; Gökçe Nur Altıkulaç; Bilge Teksin; Halime Başaran; Melike Akbay (Hacettepe University Faculty of Health Sciences Journal, 2026)
Objectives: This study aimed to evaluate the presence of food colourants, types of fat, and sustainability labels in packaged snack products for children and adolescents, based on on-label declarations of E-coded additives, without distinguishing between artificial and natural or nature-identical colourants.Materials and Methods: The study examined 405 packaged products from eight supermarket chains in Ankara, Türkiye. Product labels were assessed for content, type of fat, and sustainability indicators, including recyclable packaging, green dot, fair trade, good agricultural practices, and carbon footprint. Data were analysed using frequency and percentage distributions.Results: Colourants were found in 60.7% of the products, with beta-carotene (E160a), a commonly natural or nature-identical colourant, being the most frequently declared. Fats were present in 60% of the products, predominantly palm oil. While 61.7% of the products carried at least one eco-label, more comprehensive indicators—such as fair trade, good agricultural practices, and carbon footprint—were absent. Conclusion: The widespread use of additives and fats in snacks marketed to children contrasts with the limited diversity of sustainability labels. These findings highlight the need for policy action to enhance consumer awareness and support the development of healthier and more sustainable food environments.